A Rapid Bedside Screen to Predict Unplanned Hospitalization and Death in Outpatients With Cirrhosis: A Prospective Evaluation of the Clinical Frailty Scale. (December 2016) - Tandon, Puneeta; Tangri, Navdeep; Thomas, Lesley; Zenith, Laura; Shaikh, Tahira; Carbonneau, Michelle; Ma, Mang; Bailey, Robert J; Jayakumar, Saumya; Burak, Kelly W; Abraldes, Juan G; Brisebois, Amanda; et al.
Abstract : OBJECTIVES: Screening tools to determine which outpatients with cirrhosis are at highest risk for unplanned hospitalization are lacking. Frailty is a novel prognostic factor but conventional screening for frailty is time consuming. We evaluated the ability of a 1 min bedside screen (Clinical Frailty Scale (CFS)) to predict unplanned hospitalization or death in outpatients with cirrhosis and compared the CFS with two conventional frailty measures (Fried Frailty Criteria (FFC) and Short Physical Performance Battery (SPPB)). METHODS: We prospectively enrolled consecutive outpatients from three tertiary care liver clinics. Frailty was defined by CFS >4. The primary outcome was the composite of unplanned hospitalization or death within 6 months of study entry. RESULTS: A total of 300 outpatients were enrolled (mean age 57 years, 35% female, 81% white, 66% hepatitis C or alcohol‐related liver disease, mean Model for End‐Stage Liver Disease (MELD) score 12, 28% with ascites). Overall, 54 (18%) outpatients were frail and 91 (30%) patients had an unplanned hospitalization or death within 6 months. CFS >4 was independently associated with increased rates of unplanned hospitalization or death (57% frail vs. 24% not frail, adjusted odds ratio 3.6; 95% confidence interval (CI): 1.7–7.5; P =0.0008) and there was a dose response (adjusted odds ratio 1.9 per 1‐unit increase in CFS, 95% CI: 1.4–2.6; P <0.0001). Models including MELD, ascites, and CFS >4 had a greater discrimination (c‐statistic=0.84) than models using FFC or SPPB. CONCLUSIONS: Frailty is strongly and independently associated with an increased risk of unplanned hospitalization or death in outpatients with cirrhosis. The CFS is a rapid screen that could be easily adopted in liver clinics to identify those at highest risk of adverse events.